Recent advances in carbon nanotube patterning technologies for device applications - Kim, Yoosuk; Kuljanishvili, Irma (Frontiers in Carbon, 2023)
Carbon nanotubes (CNTs) have gained significant attention in the scientific and technology sectors due to their exceptional physical, chemical, and electronic properties. These qualities make them excellent candidates for several electronic applications, such as ballistic conduction, high current densities, low power consumption, outstanding single-photon capacity, and excellent nanomechanical resonators. However, incorporating CNTs into specific micro-and nano-architectures and hybrid structures remains challenging. Developing fabrication and patterning technologies, involving CNTs, that can scale up while utilizing their exceptional properties has received significant attention in the last two decades. Various approaches have been investigated, including top-down and bottomup methods, and new techniques have been used to achieve selective CNTs production through patterning. The continued developments of patterning technologies is critical for fully exploiting CNTs' practical applicability. This mini-review looks at recent advances in fabrication and patterning of CNTs with micro-and nanoscale resolution, such as using pre-patterned substrates, dielectrophoresis, oxidative etching, and selective production and growth for CNTs, or direct printing of CNT-containing inks, etc. Article discusses advantages and limitations of various approaches for achieving accurate and scalable CNT patterning. Overcoming fabrication challenges will pave the way for a widespread use of CNTs in various applications including electronics, photonics, mechanical and biomedical devices and hybrid systems, etc.